Strong D* -> D pi and B* -> B pi couplings - El-Bennich, Bruno [UNESP]; Ivanov, Mikhail A.; Roberts, Craig D. (Amer Physical Soc, 2011)
We compute g(D*D pi) and g(B*B pi) using a framework in which all elements are constrained by Dyson-Schwinger equation studies of QCD and therefore incorporates a consistent, direct, and simultaneous description of light and heavy quarks and the states they may constitute. We link these couplings with the heavy-light-meson leptonic decay constants and thereby obtain g(D*D pi) = 15.9(-1.0)(+2.1) and g(B*B pi) = 30.0(-1.4)(+3.2). From the latter, we infer (g) over cap (B) = 0.37(-0.02)(+0.04). A comparison between g(D*D pi) and g(B*B pi) indicates that when the c quark is a system's heaviest constituent, Lambda(QCD)/m(c)-corrections are not under good control.